Toxicological Assessment and Risk Management of Pharmaceutical Impurities - Kumar*, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
The presence of impurities in pharmaceutical products poses significant toxicological and regulatory concerns, necessitating systematic assessment and risk management strategies. Pharmaceutical impurities, which may arise from synthesis, degradation, or contamination, can compromise drug safety and efficacy. This report provides a concise overview of the principles underlying the toxicological evaluation of these impurities, emphasizing Threshold of Toxicological Concern (TTC) approaches, structure-activity relationships, and genotoxicity assessment. Regulatory frameworks, including guidelines from the International Council for Harmonisation (ICH) Q3A/B, are discussed to highlight standardised limits and reporting requirements. Risk management strategies focus on identifying, quantifying, and controlling impurities throughout the drug development and manufacturing lifecycle. Analytical techniques such as High-Performance Liquid Chromatography (HPLC), mass spectrometry, and Nuclear Magnetic Resonance (NMR) spectroscopy are crucial for accurate detection and characterisation of trace-level impurities. The integration of predictive toxicology models and in vitro assays aids in prioritising impurities that pose significant health risks, enabling efficient allocation of resources for a detailed investigation. The report also outlines application of risk-based impurity assessment, demonstrating how a combination of toxicological data, exposure analysis, and regulatory guidance can inform safe pharmaceutical development. The effective management of pharmaceutical impurities is essential for ensuring patient safety, regulatory compliance, and the sustained quality of therapeutic products. The report underscores the need for continued advancements in analytical methodologies and predictive toxicology to address emerging challenges in impurity risk assessment.
Keywords: Genotoxicity; Pharmaceutical impurities; Risk management; Threshold of toxicological; concern; Toxicological assessment